Income Tax: Genesis of Definition and Object of Accounting - G. BASHYROVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
Income tax in many countries is one of the main sources of filling the public budget and levers of influence on the development of economic processes at the macro level. The income tax ensures the balance of economic interests of the state, legal entities and individuals and the avoidance of excessive tax pressure. The impact of European integration processes on the Ukrainian accounting system increases the relevance of the development of the organization and methods of accounting for income tax. The purpose of the article is to establish the main phases of the evolution of the concept of “income tax”, clarify its economic content and identify the characteristics as an object of accounting.The article examines the historical phases of the income tax evolution, taking into account amendments in the tax law in Ukraine. A review of interpretations of the concept of “income tax” by foreign and domestic scholars was made, to establish the three main approaches to its interpretation: as a direct tax paid by a business entity from the received profit; as an item of the company financial statement, informing concerned parties on the amount of the assessed and paid tax; as a company’s payment to the state for utilization of economic infrastructure and resources. The author’s definition of the concept of “income tax” is proposed, which contributes to the clarification of the accounting terminology. It is argued that income tax should be considered through the prism of the tax law and accounting standards. A comparison of treatment to income tax as an accounting object in the National Accounting Standard 17 “Tax Income” and International Accounting Standards 12 “Income Taxes” is made. Based on a study of the legal framework for the accounting of income tax, its main components are identified as an object of accounting.